Terms sustainable collaboration heterogeneous asynchronous machine in an autonomous electromechanical complex - Mishin, V.; Chuyenko, R.; Makarevich, S. (Energy and Automation, 2015)
To ensure stable conditions of the established heterogeneous asynchronous generator and engine power commensurate offline proposed distribution of complex electromechanical excitation volume machines on individual branches of the circuit, unrelated conditions ferorezonansu stress.